Six-day westward propagating wave in the maximum electron density of the ionosphere - D. Altadill (Annales Geophysicae, 2003)
Analyses of time-spatial variations of critical plasma frequency foF2 during the summer of 1998 reveal the existence of an oscillation activity with attributes of a 6-day westward propagating wave. This event manifests itself as a global scale wave in the foF2 of the Northern Hemisphere, having a zonal wave number 2. This event coincides with a 6-day oscillation activity in the meridional neutral winds of the mesosphere/lower thermosphere (MLT). The oscillation in neutral winds seems to be linked to the 6–7-day global scale unstable mode westward propagating wave number 1 in the MLT. The forcing mechanisms of the 6-day wave event in the ionosphere from the wave activity in the MLT are discussed. Key words. Ionosphere (Ionosphere-Atmosphere interactions; Mid-latitude Ionosphere) – Meterology and atmospheric dynamics (waves and tides)